Study of the Effect of Polyethylene Resin Particle Size on the Degree of Fluidized Bed Reactor Electrification and Wall Fouling - Tian, Ye (Université d'Ottawa / University of Ottawa, 2014)
In gas-solid fluidized bed reactors, such as those employed for polyethylene production, the generation of electrostatic charge is almost unavoidable. Electrostatic charges are generated due to the continuous contacts between particles and particles and the reactor wall. In such processes, accumulation of electrostatic charge causes a layer of particles to adhere to the reactor wall, a problem known as “sheeting” in polyolefin industry. Sheeting results in frequent reactor shutdowns for clean-up and in turn significant economic loss. The overall focus of this research is to better understand the underlying mechanisms of charge generation in gas-solid fluidized beds to ultimately be able to find means to reduce or eliminate this problem. The specific objective of this thesis is to determine the effect of fluidizing particle size on the degree of bed electrification and reactor wall coating. The experimental program involved the fluidization of polyethylene resins received directly from commercial reactors (i.e., having a wide size distribution of 20-1500 micron), as well as mono-sized large particles (600-710 micron) and binary mixture of small particles (200-300 micron and 300-425 micron with fractions up to 20 wt%) and large particles (600-710 micron). Experiments were carried out under atmospheric conditions in 3D fluidization columns housing two Faraday Cups for electrostatic charge measurement. For all conditions, the charge, mass and size distribution of particles fouled on the reactor wall as well as the layer thickness were measured and compared. Fluidization of the resins as received resulted in a certain size of particles (400 µm and smaller) to adhere to the column wall. For binary mixtures, the particles layer formed on the reactor wall mainly consisted of the smaller particles. Although the extent of wall coating declined as the amount of the smaller particles increased, but the smaller particles had a much higher net specific charge and thus replaced the large particles within the wall coating. Such high charge of small particles accumulated on the column wall in turn prevented the wall coating growth due to repelling the oppositely charged particles to the bulk of the bed. Regardless of the charge polarity of the bulk and wall particles, the wall fouling formation mechanism was found to be similar. Between the two sizes of small particles tested, the 212-300 micron particles gained a higher net specific charge than 300-425 micron particles. Bipolar charging due to small and large particles contacts was detected within the bulk of the bed and the wall coating.
Keywords: fluidized bed; electrostatics; particle size